2005
DOI: 10.1128/cdli.12.2.363-365.2005
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Intracranial Granulomas and Cerebrospinal Fluid Levels of Gamma Interferon and Interleukin-10 in Patients with Tuberculous Meningitis

Abstract: Cerebrospinal fluid gamma interferon (IFN-␥) and interleukin-10 levels in 39 patients with tuberculous meningitis were serially measured. Cytokine levels did not predict intracranial granuloma (IG) development, but IFN-␥ levels in the top quartile after 1 month of therapy were highly associated (odds ratio ‫؍‬ 18) with detection of an IG by computed tomography scanning.Cytokines such as gamma interferon (IFN-␥) and tumor necrosis factor alpha play a pivotal role in the development of granulomas in pulmonary tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Lu et al also determined that in 10 of these TBM patients the average CSF IFN-γ levels were 500.48 pg/mL before treatment and 103.62 pg/mL following 4 weeks of treatment, indicating that while IFN-γ decreased significantly (5-fold), it still remained elevated compared to the norm, after 4 weeks of treatment (that is, inflammation in the brain persisted). Mansour et al (2005) reported a highly elevated mean concentration of CSF IFNγ (794 ± 530 pg/mL) in 39 patients with TBM (all of whom were HIV negative) prior to receiving medication, which was correlated with markers of neuroinflamation in these individuals. Mansour et al (2005) also showed that the CSF IFN-γ remained elevated for many weeks after treatment was begun in patients with TBM, whereas in those cases diagnosed with VM and BM the CSF IFN-γ returned to undetectable concentrations within a couple of days post-treatment.…”
Section: Interferon-γmentioning
confidence: 95%
See 1 more Smart Citation
“…Lu et al also determined that in 10 of these TBM patients the average CSF IFN-γ levels were 500.48 pg/mL before treatment and 103.62 pg/mL following 4 weeks of treatment, indicating that while IFN-γ decreased significantly (5-fold), it still remained elevated compared to the norm, after 4 weeks of treatment (that is, inflammation in the brain persisted). Mansour et al (2005) reported a highly elevated mean concentration of CSF IFNγ (794 ± 530 pg/mL) in 39 patients with TBM (all of whom were HIV negative) prior to receiving medication, which was correlated with markers of neuroinflamation in these individuals. Mansour et al (2005) also showed that the CSF IFN-γ remained elevated for many weeks after treatment was begun in patients with TBM, whereas in those cases diagnosed with VM and BM the CSF IFN-γ returned to undetectable concentrations within a couple of days post-treatment.…”
Section: Interferon-γmentioning
confidence: 95%
“…Mansour et al (2005) reported a highly elevated mean concentration of CSF IFNγ (794 ± 530 pg/mL) in 39 patients with TBM (all of whom were HIV negative) prior to receiving medication, which was correlated with markers of neuroinflamation in these individuals. Mansour et al (2005) also showed that the CSF IFN-γ remained elevated for many weeks after treatment was begun in patients with TBM, whereas in those cases diagnosed with VM and BM the CSF IFN-γ returned to undetectable concentrations within a couple of days post-treatment. Considering all of the above, patients with VM and TBM exhibit a similar increase in CSF IFN-γ levels, both far greater than in patients with BM.…”
Section: Interferon-γmentioning
confidence: 95%
“…CSF IL6 concentration at the time of presentation was independently associated with severity of disease [49]. Levels of IFNγ and IL10 did not predict the development of intracranial granuloma in TBM [50]. In a recent study IL1β, IL6, IL8 and IL10 were expressed in the initial stage of TBM and declined significantly with therapy but were not related to the stage of meningitis and its outcome [51].…”
Section: Molecular Pathogenesis Of Stroke In Tuberculous Meningitismentioning
confidence: 97%
“…The mechanism behind the progression or development of intracranial tuberculomas after treatment remains a subject of speculation. It has been reported that the paradoxical tuberculomas were attributable to several factors such as exaggerated immune responses occurring on ATT, the virulence of the tubercle bacilli, the site of infection, the antigen load, hypersensitivity to tuberculosis, and chemotherapeutic regimen (Afghani and Lieberman, 1994;Ranjan et al, 2003;Cheng et al, 2003;Unal and Sutlas, 2005;Gupta et al, 2003;Mansour et al, 2005;Davis and Ramakrishnan, 2009). A therapy-induced transient worsening of cerebrospinal fluid (CSF) parameters is also frequently observed during treatment, such as an initial lymphocytic reaction may change in the direction of neutrophil predominance (Singh et al, 2016;Sutlas et al, 2003;Tai et al, 2016;Cheng et al, 2003;Garcia-Monco et al, 2005;Teoh et al, 1986).…”
Section: Introductionmentioning
confidence: 99%